Serial jako medium edukacyjne, czyli młodzież i rodzina w serialach „Euforia” i „13 powodów” - Płowuszyńska , Martyna (Studia Edukacyjne, 2022)
Popular culture surrounds us all and becomes an indispensable part of our lives, which is why it is important to conduct research in this field. The article is based on two series dedicated to youth, Euforia and 13 Reasons Why. In this text, I described the educational potential of popular culture, introduced the phenomenon of the series and mentioned these types. Moreover, I included information about what attracts the viewer to this type of audiovisual messages. The dominant topic in this analysis of the series is the intra-family relations of young people. I described parenting styles, relationships in adolescent families, family types, conflict issues in families, and the trust and au- tonomy of adolescents. The crucial important issue of social, emotional and spiritual orphanage was raised, too.